Korelasi Pemilu Serentak dengan Multi Partai Sederhana Sebagai Penguatan Sistem Presidensial - Hayat Hayat (The Constitutional Court of the Republic of Indonesia, 2014)
Constitutional Court Decision No. 14/PUU-XI/2013 mandated national elections simultaneously between elections executive (President and Vice-President) and legislative (House of Representatives, Provincial and District/City). After the 1945 amendment to experience a variety of complications in the Indonesian political system nationally. Democratization deliver the Indonesian people switching system of government, ie from a presidential system to the parliamentary system. Elections as a democratic process to the leadership of the government elected by the people as a sovereign State. The system of government by consensus of the people, by the people and for the people has implications for improving the effectiveness and stability of the country. The Problem is the electoral system with the current political party system is less effective in the election which is actually held separately between the presidential election, and the election pileg. Giving rise to various problems of the complexity of government (central and local governments). In the hierarchy, the presidential system is less relevant to the separate electoral system between national elections (pileg and presidential) election and the multi-party system. Political reality with the current system adopted, lead to conflicts among constituents, a very high political costs for the government and the candidates (candidates), strengthening of money politics is difficult to avoid the impact of a majority vote, a negative effect on the psychology of candidates when lost or won in battle politics, coalitions are not “healthy” in the implementation of the government, due to various political ideologies and individual interests, as well as the problems of the strategic policies of government. The correlation between electoral systems simultaneously with a multi-party system is a simplified alternative solution in presidential systems strengthening to improve the welfare of the whole people of Indonesia.